Network security : - Maiwald, Eric (McGraw-Hill/Osborne, 2003)
All companies rely on some security mechanisms to ensure their corporate privacy and information integrity. In many cases, the ability of the technician to explain a system's vulnerabilities to managers in order to acquire funding is as important as the technical skills to build the system. This book addresses a wide range of topics, from security basics to policies, practices, and practical solutions. Though intended for network administrators, this also acts as a good primer on security concepts for the lay computer user